2018
DOI: 10.1164/rccm.201707-1500im
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Gain of Function: A New Kid on the Block in Interstitial Lung Diseases

Abstract: C.D. were involved in clinical follow-up of the patient, participated in the conceptualization and design of the case report, contributed to the acquisition of data, critically revised the manuscript, and approved the final manuscript as submitted; M. Baque participated in the conceptualization and design of the case report, contributed to the acquisition of the computed tomography scan, critically revised the manuscript, and approved the final manuscript as submitted; D.A. participated in the conceptualizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 5 publications
1
33
0
Order By: Relevance
“…As for PID associated ILD, it has been recognized that PID may be associated with immune-mediated ILD especially in auto-inflammatory disorders, diseases of immune dysregulation, and predominantly antibody deficiencies such as CVID [11][12][13][14][15][16][17][18][19][20]. Two new auto-inflammatory disorders SAVI and COPA syndrome which has been reported to be associated with ILD [15][16][17] were both found in our study cohort.…”
Section: Discussionsupporting
confidence: 50%
“…As for PID associated ILD, it has been recognized that PID may be associated with immune-mediated ILD especially in auto-inflammatory disorders, diseases of immune dysregulation, and predominantly antibody deficiencies such as CVID [11][12][13][14][15][16][17][18][19][20]. Two new auto-inflammatory disorders SAVI and COPA syndrome which has been reported to be associated with ILD [15][16][17] were both found in our study cohort.…”
Section: Discussionsupporting
confidence: 50%
“…Association between STAT3 and the onset of senescence are well documented (reviewed in (47)) and STAT3 activity is strongly associated with interstitial lung diseases such as IPF (35,(48)(49)(50). In this study, we identified STAT3 as playing a key role in the shift of secretory profile, cell cycle arrest, and mitochondrial respiration.…”
Section: Discussionmentioning
confidence: 74%
“…Patients with germline STAT3 GOF mutations have been associated with early-onset multiorgan autoimmunity, lymphoproliferation, early-onset growth failure, and may have severe recurrent infections. Studies have also shown an association of STAT3 GOF with interstitial pneumonitis and role of STAT3 signaling in interstitial and fibrotic lung disease pathogenesis 14…”
Section: Introductionmentioning
confidence: 97%